Nurturing Ethical Character in Islamic Colleges through Interactive Technology: Lecturers Perspective - Rabbianty, Eva Nikmatul; Siti Azizah; Mashur Abadi; Nina Khayatul Virdyna; Ali Said Al-Matari (TADRIS: Jurnal Pendidikan Islam, 2023)
This article examines the impact of integrating interactive technology in character education programs on ethical character development in Islamic colleges from the lecturers' perspective. The study addresses two research questions: (1) How does the integration of interactive technology influence ethical character development, according to lecturers in Islamic colleges? (2) What challenges do lecturers face in effectively utilizing interactive technology for nurturing ethical character education?. Data was collected through a survey of 50 lecturers from Islamic colleges in Madura, using a combination of closed-ended and open-ended questions. The findings reveal that integrating interactive technology positively affects ethical character development by enhancing student engagement, critical thinking, and moral reasoning. This research contributes to addressing a research gap by providing empirical evidence on the effectiveness of interactive technology in nurturing ethical character development in the context of Islamic colleges. Additionally, the study identifies challenges lecturers face in embracing the digital age, including limited technical skills, inadequate resources, and resistance to change. Addressing these challenges is crucial for maximizing the potential of interactive technology in character education programs. Overall, this research offers practical insights for educational institutions and policymakers, informing the design of strategies for incorporating interactive technology into character education programs while mitigating associated challenges. By focusing specifically on Islamic colleges, this study provides unique perspectives on integrating interactive technology in nurturing ethical character development, adding novelty to the existing literature